A laboratory-scale annular continuous flow reactor for UV photochemistry using excimer lamps for discrete wavelength excitation and its use in a wavelength study of a photodecarboxlyative cyclisation - DeLaney, Erica N.; Lee, Darren S.; Elliott, Luke D.; Jin, Jing; Booker-Milburn, Kevin; Poliakoff, Martyn; George, Michael W. (Royal Society of Chemistry, 2016)
This paper describes a new annular reactor for continuous UV photochemistry, which uses easily interchangeable excimer lamps of different wavelengths. The reactor has narrow clearance to form thin films of material for efficient irradiation of molecules. Its use is demonstrated by investigating the effect of discrete wavelength lamps (222, 282 and 308 nm) on the reaction of potassium N-phthalimidobutanoate 1. The ability of the reactor to be integrated into multistep processes is illustrated by combining it with an Amberlyst scavenger and a solid acid catalyst, NbOPO4, to access a second product 3 that is obtained in a single telescoped process. The tricyclic scaffold in 3 is a motif found in several biologically active compounds and has possibilities as a synthon for new pharmaceutical products.